PERANCANGAN WEB EDUKASI KRIPTOGRAFI DASAR - Octavianus, Jaeson; Hakim, Lukman (Universitas Bunda Mulia, 2023)
Cryptography is a science or art that is useful for maintaining the confidentiality of letters by converting messages into forms that are no longer understood (Simargolang, 2017). Many students feel that the dissemination of cryptographic information that is disseminated is still ineffective, because there are still many students who do not really understand cryptography so they have to surf the internet, read books, etc. to find additional information. The purpose of this research is to create applications that are effective and can be a medium for disseminating information for students about cryptography to develop their level of knowledge of cryptography and to disseminate additional information about cryptography through cryptography educational applications. The data collection technique used in this research is by conducting a literature study and collecting primary data. The data used is obtained from conducting a survey using google form and is used to determine decisions in making the